Overcoming water scarcity and quality constraints: Water Harvesting and Watershed Management - Kerr, John M.; Pangare, Ganesh (International Food Policy Research Institute, 2001)
The world’s freshwater shortages result more from uneven distribution of water over time and space than from absolute scarcity. Even in some of the world’s highestrainfall areas, rain falls in concentrated periods followed by prolonged dry spells, so users must capture rainwater when it is abundant to use later when it is scarce.